PCSK9 polymorphism in a Tunisian cohort: Identification of a new allele, L8, and association of allele L10 with reduced coronary heart disease risk. Issue 1 (February 2015) - Slimani, Afef; Hrira, Mohamed Yahia; Najah, Mohamed; Jomaa, Walid; Maatouk, Faouzi; Hamda, Khaldoun Ben; Abifadel, Marianne; Rabès, Jean-Pierre; Boileau, Catherine; Rouis, Mustapha; Slimane, Mohamed Naceur; Varret, Mathilde
Abstract: The c.61_63dupCTG (L10) allele of rs72555377 polymorphism in PCSK9 has been reported to be associated with low-density lipoprotein-cholesterol (LDL-C) levels and with a decreased risk of coronary artery disease (CAD). We investigated the effect of two known alleles for rs72555377, L10 and L11, on the risk of CAD in a Tunisian cohort (218 patients diagnosed by angiography and 125 control subjects). Two subgroups of patients were defined by their level of stenosis: ≥50% for CAD and <50% for no-CAD. The genotypes were obtained by the size measurement of fluorescent-labeled PCR products. We identified a novel allele for the rs72555377 polymorphism: an in-frame deletion, c.61_63delCTG (L8). The frequency of the L10 allele was significantly higher in the no-CAD subgroup than in the CAD subgroup (0.210 vs 0.114, p  = 0.045), and than in the subgroup of CAD patients presenting a stenosis ≥50% in two or three major coronary arteries (0.210 vs 0.125, p  = 0.028). Multiple regression analysis showed that the L10 allele was significantly associated with a reduced risk of CAD ( p  = 0.049, OR = 0.51[0.26–1.00]), and with its reduced severity ( p  = 0.045, OR = 0.44[0.20–0.98]). The L10 allele is associated with a reduced risk and severity of CAD, seemingly independently of its LDL-lowering effect, suggesting a direct effect of PCSK9 on atherogenesis.